The last lion, Winston Spencer Churchill : Alone, 1932-1940 - Manchester, William, 1922-2004. (Boston : Little, Brown, 1988)
The noted biographer-historian continues his life of Winston Churchill, focusing here on the years of Churchill's political exile and his increasingly forceful opposition to Hitler's Germany.
v. 2. Alone, 1932-1940.
Includes bibliographical references and index.
Keywords: Churchill, Winston, -- 1874-1965.; Great Britain -- Politics and government -- 1901-1936.; Great Britain -- Foreign relations -- 1936-1945.; Great Britain -- Foreign relations -- 1910-1936.; Prime ministers -- Great Britain -- Biography; Churchill, Winston, -- 1874-1965 -- Sir).; Grande-Bretagne -- Politique et gouvernement -- 1901-1936.